PENGETAHUAN SUAMI TERHADAP KESEHATAN ISTERI DEMI HUBUNGAN HARMONIS DALAM RUMAH TANGGA - Mutia Sofia; Indra Wijaya (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Health is a very important thing, especially with regard to the household. The study in this research is literature taken from theory, both journals and books. The results showed that; Households are formed because of love and eventually build a household mahligai. However, to maintain a harmonious relationship in the family, it is also necessary to know how to maintain health, especially against diseases that are often suffered by women. Therefore, the importance of health and knowledge for a husband about his wife's health problems, with the aim of maintaining a harmonious relationship.